UJI DAYA HAMBAT EKSTRAK LIDAH BUAYA (Aloe vera l.) TERHADAP PERTUMBUHAN Staphylococcus aureus - AMIN LUBIS, M. RIZQI; MOURISA, CUT (LP2MTBM MAKARIOZ, 2023)
The use of antibacterial is a solution to treat various infectious diseases. However, the mismatch of the dose given can lead to bacterial resistance to these antibacterial substances. So, it is necessary to renew or develop natural medicines to kill bacteria and prevent resistance. One type of plant that can be used as a natural antibacterial is aloe vera (Aloe vera L.) because it contains several active substances including saponins, flavonoids, tannins and polyphenols which are thought to have antibacterial activity. This study used an experimental method with a laboratory observation approach. the results showed that aloe vera extract (Aloe vera L.) in all concentration groups (20%, 40%, 60%, 80%, and 100%) had a significant difference. with a probability value (p) <0.05, which means that aloe vera extract is effective in inhibiting the growth of Staphylococcus aureus bacteria. The conclusion here is Aloe vera extract ( Aloe Vera L) is effective in inhibiting the growth of Staphylococcus aureus